CONSTRUCTION AND RE-CONCEPTION OF IDENTITY: REJECTING HOMOGENEITY IN AMERICA THROUGH THE VANISHING HALF (2020) BY BRIT BENNETT - Nadiah Surya Nahari; Bayu Kristianto (Universitas Nasional, 2023)
Identity shows one's identification in a social context, but in fact social conditions still tend to require citizens to identify themselves based on skin color and sexuality that has been determined and deemed appropriate. Such conditions are seen as homogenizing behavior. The Vanishing Half (2020) establishes the identity of its characters as a rejection of the homogeneity of skin color and sexuality in America. The rejection is reflected in the identity construction of the characters in The Vanishing Half (2020) which features mulatto people to show that skin color identities are not only black or white but can vary widely, and presents transsexual characters to show that a person's sexual identity is not just limited to naturally men and women. The identity construction of the characters is carried out to redefine the concept of identity in a fluid social society. Identity re-conception is carried out as an effort to build awareness of the concept of identity which is fluid, layered, changeable and diverse, so it is necessary to carry out legal protection of identity.